Apreciaciones relativas a las manifestaciones de la responsabilidad social empresarial como declaración unilateral de voluntad - López Jiménez, David (2013)
It is very well known that, nowadays, a large number of companies participate, in a particularway, in actions that can be included in what is called Corporate Social Responsibility. Althoughthe scores of the documents in which it is included are relatively numerous, when it is implantedand implemented by the own company –without the existence of an external organism which isimpartial and independent for its verification– have the common mark of the establishment, froma legal point of view, of a unilateral declaration of will.